2018
DOI: 10.1523/jneurosci.2673-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Loss of eIF4E Phosphorylation Engenders Depression-like Behaviors via Selective mRNA Translation

Abstract: The MAPK/ERK (mitogen-activated protein kinases/extracellular signal-regulated kinase) pathway is a cardinal regulator of synaptic plasticity, learning, and memory in the hippocampus. One of major endpoints of this signaling cascade is the 5′ mRNA cap binding protein eIF4E (eukaryotic Initiation Factor 4E), which is phosphorylated on Ser 209 by MNK (MAPK-interacting protein kinases) and controls mRNA translation. The precise role of phospho-eIF4E in the brain is yet to be determined. Herein, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…S10A-B). This parallels previous findings that Mnk1/2 controls the translation of a specific subset of mRNAs (19,26). Paclitaxel-treated mice given eFT508 after full development of CIPN showed a dose-related reversal of mechanical and thermal hypersensitivity (Fig.…”
Section: Neuronssupporting
confidence: 90%
“…S10A-B). This parallels previous findings that Mnk1/2 controls the translation of a specific subset of mRNAs (19,26). Paclitaxel-treated mice given eFT508 after full development of CIPN showed a dose-related reversal of mechanical and thermal hypersensitivity (Fig.…”
Section: Neuronssupporting
confidence: 90%
“…While the current study was being considered for publication, a different research group reported depression-like behaviors and increased inflammatory responses in the Eif4e ki/ki mice 66 . Behavioral phenotypes in our Eif4e ki/ki mouse testing are consistent with those reported by reference 66 .…”
Section: Discussionmentioning
confidence: 96%
“…While the current study was being considered for publication, a different research group reported depression-like behaviors and increased inflammatory responses in the Eif4e ki/ki mice 66 . Behavioral phenotypes in our Eif4e ki/ki mouse testing are consistent with those reported by reference 66 . In addition, our study demonstrated the involvement of MNK1 and MNK2 as the upstream kinases of eIF4E, and demonstrate the involvement of TNFα as a mediator of serotonergic neurotransmission impairment in the PFC and the DR, as a consequence of decreased eIF4E phosphorylation and attenuated translation of the mRNA encoding IκBα.…”
Section: Discussionmentioning
confidence: 96%
“…In the brain, eIF4E phosphorylation controls the translation of mRNAs involved in inflammatory responses such as IκBα, a repressor of the transcription factor NF-κB that regulates the expression of the cytokine tumor necrosis factor (TNFα) ( Aguilar-Valles et al, 2018 ). Genome-wide translational profiling of the brain from eIF4E S209A mice revealed that eIF4E phosphorylation controls translation of mRNAs involved in inflammation (IL-2 and TNFα), organization of the extracellular matrix ( Prg2 , Mmp9 , Adamts16 , Acan ), and the serotonin pathway ( Slc6a4 ) ( Amorim et al, 2018 ).…”
Section: Eif4e In Regulation Of Peripheral Nociceptive Plasticitymentioning
confidence: 99%